P.032 Long-term safety and tolerability of eptinezumab in patients with chronic migraine: A 2-year, open-label, phase 3 trial. (November 2021) - Kudrow, D; Cady, R; Allan, B; Pederson, S; Hirman, J; Meessen-Pinard, M; Schaeffler, B
Abstract : Background: Eptinezumab is approved in the US for the preventive treatment of migraine and was well tolerated in double-blind, placebo-controlled studies in patients with episodic and chronic migraine (CM). The PREVAIL study evaluated the long-term safety, immunogenicity, and impact on patient-reported outcomes of repeat doses of eptinezumab in patients with CM. Methods: PREVAIL was an open-label, phase 3 trial comprising two 48-week treatment phases. Adults with CM received eptinezumab 300 mg by 30-minute IV every 12 weeks for ≤8 doses, with patients followed up to week 104. Results: 128 adults (mean age, 41.5y) with CM were treated. Over 2 years, the most frequently reported treatment-emergent adverse events were nasopharyngitis (14.1%), upper respiratory tract infection (7.8%), sinusitis (7.8%), influenza (6.3%), bronchitis (5.5%), and migraine (5.5%). Study-drug discontinuation due to adverse events was 6.3%. Anti-eptinezumab antibody incidence peaked at week 24 and declined despite continued dosing, to nondetectable levels at week 104. Patient-reported outcomes were improved at first assessment (week 4) and generally sustained through week 104. Conclusions: In adults with CM, eptinezumab 300 mg demonstrated a favorable safety profile, limited long-term immunogenicity, early and sustained reductions in migraine-related burden, and improvements in health-related quality of life over 2 years.